Bracing for the apocalypse : an ethnographic study of New York's 'prepper' subculture - Bounds, Anna Maria (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Increasing American fear about terrorism, environmental catastrophes, pandemics, and economic crises has fueled interest in 'prepping': confronting disaster by mastering survivalist skills. This trend of self-reliance is not merely evidence of the American belief in the power of the individual; rather, this pragmatic shift away from expecting government aid during a disaster reflects a weakened belief in the bond between government and its citizens during a time of crisis. This ethnographic study explores the rise of urban preppers, the survivalist subculture in New York City, shedding light on the distinctive approach of city dwellers in preparing for disaster. With attention to the role of factors such as class, race, gender and one's expectations of government, it shows that how one imagines Doomsday affects how one prepares for it. Drawing on participant observation, the author explores preppers' views on the central question of whether to 'bug out' or 'hunker down' in the event of disaster, and examines the ways in which the prepper economy increases revenue by targeting concerns over developing skills, building networks, securing equipment and arranging a safe locale. A rich qualitative study, Bracing for New York's Apocalypse will appeal to scholars of sociology and anthropology with interests in urban studies, ethnography and subcultures"--
Part 1. Understanding the rise of prepping in the global city of New York -- "Ready.Gov" versus "ready without gov": prepping for disaster -- New York marks the spot: living on the x -- Popular entertainment: preppers as characters and as consumers -- Part 2. Prepping in New York: going it alone or going together -- Bugging in: sheltering in place for the extremely wealthy and mere mortals -- Bugging out: strategic relocation and strategic packing -- Part 3. Urban prepping and symbolic interaction -- New York prepper's network's mission and organizational structure -- Toughing it out on the weekend -- Dodging a bullet -- Part 4. Urban prepping as a new reflection of citizenship -- Future directions for New York City prepping.
OCLC-licensed vendor bibliographic record.
Keywords: Survivalism -- Social aspects -- New York (State) -- New York; Preparedness -- Social aspects -- New York (State) -- New York; Subculture -- New York (State) -- New York; New York (N.Y.) -- Social life and customs; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General